Mature aggressive B-cell lymphoma across age groups – molecular advances and therapeutic implications. Issue 2 (1st February 2017) - Lange, Jonas; Lenz, Georg; Burkhardt, Birgit
ABSTRACT: Introduction: Mature B-cell lymphoma represents the most common type of Non-Hodgkin lymphoma, and different subtypes prevail at different patient ages. Areas covered: We review recent data on differences and commonalities in mature B-cell lymphoma occurring in adult and pediatric patients, with a special emphasis on molecular advances and therapeutic implications. To this end, we will discuss knowledge on diffuse large B-cell lymphoma and Burkitt lymphoma/leukemia, which are the most frequent subtypes in adult and pediatric patients, respectively, and on primary mediastinal B-cell lymphoma, which is a subtype of mature B-cell lymphoma occurring mainly in adolescents and young adults with a female predominance. Expert commentary: Molecular profiling has revealed molecular alterations that can be used to further classify the subtypes of mature B-cell lymphoma. These new subgroups frequently respond differentially to targeted therapeutic strategies. Future clinical trials utilizing new drugs will address this issue by combining clinical data and response assessment with a molecular workup of the corresponding lymphomas.